ROLE OF MATRA BASTI (ENEMA) OVER ABHYANGA (MASSAGE) AND SWEDA (SUDATION) IN REDUCING SPASTICITY IN CEREBRAL PALSY WITH SUDDHA BALA TAILA-A RANDOMIZED COMPARATIVE CLINICAL STUDY - A Deepti, Kurubar; Munnoli, B. T.; Vijaykumar, D.; Aziz, Arbar; Amol, Patil (International Journal of Ayurveda and Pharma Research, 2015)
Objective of the study was to assess the efficacy of Matra basti (enema) over Abhyanga (massage) and Sweda (sudation) in reducing spasticity in cerebral palsy. Study was carried out in IPD, Department of Kaumarbhritya, KLEs Shri BMK Ayurved Mahavidyalaya, Shahapur, Belgaum, Karnataka; India.30 children fulfilling diagnostic criteria between the age group of 2-12 years were included and enrolled as per computer generated block randomization into 2 groups of 15 children in each group. Group A was administered with Matra basti (enema) after local Abhyanga (massage) with Suddha bala taila and local Swedana (sudation) with Nadi sweda (type of sudation) method for a duration of 15 days. In group B spastic children were treated with Sarvanga Abhyanga (massage all over body) followed by plain Nadi sweda with Suddha bala taila. Follow up was done on 30th and 45th day of treatment. Both the procedures were helpful in reducing spasticity. Matra basti (enema) is more effective in treating the spasticity of cerebral palsy as compared to Abhyanga (massage) and Sweda, whereas Abhyanga (massage) and Sweda (sudation) is effective in treating fine motor functions. Suddha Bala taila is effective in treating Ekanga vata (monoplegia), Pakshaghata (diplegia) and other related Vata Vyadhi (neurological disorders) as attributed to its Rogaghnata (disease). Thus the procedures are effecting in reducing spasticity.